M15 Early diagnosis of lung cancer through case finding – the liverpool healthy lung program two years on. (December 2018) - Ledson, MJ; Tippett, V; Arvanitis, R; Timoney, M; Gaynor, E; Field, J
Abstract : High risk case finding/screening for lung cancer is now becoming more widespread, and to aid this NHS England has produced a consultation document 'Specification for targeted early detection/Screening for Lung Cancer with low radiation dose computer tomography'. Through the Liverpool Healthy Lung Program we have been carrying out targeted case finding since 2016, and we now present our 2 year experience. Primary care services identify high risk patients (significant smokers, asbestos exposure, or COPD diagnosis) and those aged between 58 and 75 are invited to a 'lung health check', which includes a lifestyle review with onward referral to smoking cessation, dietetics, and exercise programs where appropriate. A lung cancer risk score ('My Lung Risk') is calculated: high risk patients are offered a CT scan, and those not diagnosed with COPD are offered spirometry. The service aims to have been rolled out to whole of the city by 2020. At May 2018, of 13 761 people invited to the lung health check, 5569 (40%) had attended and 1968 (35%) had reported scans. There were 37 confirmed cases of lung cancer (1.9%), of which 76% were stage 1 and 2 and treated with curative intent. 3508 (63%) underwent spirometry and 10% of all those tested went on to be diagnosed with COPD. 177 (9%) scans identified nodules requiring follow up, and 177 (9%) major clinically significant other findings (other cancers, aneurysms, bronchiectasis etc.). Independent patient evaluation shows that 98% felt better about their lung health after the check, 99% were satisfied or very satisfied with the process, and 97% reported they would encourage or strongly encourage a friend to participate. The project is CCG funded (£400K per annum) and has staff and scanning services embedded within existing NHS structures for continuity and sustainability, at current pace. External evaluation has calculated 13K per QALY (this does not include benefits of smoking cessation or diagnosing COPD). We are now planning a second round in the city, and are negotiating with neighbouring CCGs, our cancer alliance and NHS England to roll this service out across our cancer network.